Re-living the American frontier : western fandoms, reenactment, and historical hobbyists in Germany and America since 1900 - Reagin, Nancy Ruth, 1960- (Fandom & culture., 2021)
"The past offers a pleasant refuge from the present for many people, including historical reenactors and other historically-focused fan communities. Historical reenactment and living history groups extend far beyond modern hobbyists who recreate American Civil War battles (probably the best known type of historical reenactment) and go back more than a century in the United States and Europe. Many of these fandoms were inspired by literary works that vividly depicted idealized, romanticized historical cultures. These fans have received relatively little attention from either historians or scholars of popular culture. The historic and mythic elements of the American Old West--covered wagon trains, stockade forts, herds of buffalo that stretch as far as the eye can see, teepee villages, Indian warriors on horseback, cowboys on open ranges, and white settlers "taming" a wilderness with their plows and log cabins--have exerted a global fascination over 200 years, and became the foundation for fan communities that have endured for generations. Artists, writers, entertainment media, and quite ordinary people around the world have mined Old West images, tropes, and settings for almost two centuries, often with joyful absorption and fascinated attention to the artifacts and cultures of the West. This book examines some of those fan communities, particularly German fans originally inspired by the Western novels of Karl May, and American enthusiasts of Laura Ingalls Wilder's Little House on the Prairie series. But the Old West (like all visions of the past) proved to be shifting cultural terrain, as each generation rewrites its own past. In both Germany and the U.S., Western fan communities were initially uncontroversial, since Western narratives of white settlement were seen as "unpolitical" and generally widely accepted by both white Americans and Europeans. But in Germany, the American West was reevaluated and politically repurposed during the Nazi period, and in both East and West German culture. During the late twentieth century, popular understandings of the West (and scholarly ones) changed in the United States as well, as white colonial settlement and the displacement of Native American cultures became a flashpoint in the culture wars between right and left. Ultimately, the past that fan communities sought to recreate was reshaped by the changing present, as each generation of fans adapted and recreated their own West"--